Visual mechanisms for voice‐identity recognition flexibly adjust to auditory noise level - Maguinness, Corrina (Hum Brain Mapp, 2021)
Recognising the identity of voices is a key ingredient of communication. Visual mechanisms support this ability: recognition is better for voices previously learned with their corresponding face (compared to a control condition). This so‐called ‘face‐benefit’ is supported by the fusiform face area (FFA), a region sensitive to facial form and identity. Behavioural findings indicate that the face‐benefit increases in noisy listening conditions. The neural mechanisms for this increase are unknown. Here, using functional magnetic resonance imaging, we examined responses in face‐sensitive regions while participants recognised the identity of auditory‐only speakers (previously learned by face) in high (SNR −4 dB) and low (SNR +4 dB) levels of auditory noise. We observed a face‐benefit in both noise levels, for most participants (16 of 21). In high‐noise, the recognition of face‐learned speakers engaged the right posterior superior temporal sulcus motion‐sensitive face area (pSTS‐mFA), a region implicated in the processing of dynamic facial cues. The face‐benefit in high‐noise also correlated positively with increased functional connectivity between this region and voice‐sensitive regions in the temporal lobe in the group of 16 participants with a behavioural face‐benefit. In low‐noise, the face‐benefit was robustly associated with increased responses in the FFA and to a lesser extent the right pSTS‐mFA. The findings highlight the remarkably adaptive nature of the visual network supporting voice‐identity recognition in auditory‐only listening conditions.